The internal armed conflict in Colombia. Background and perspectives. - Vargas, Alejo (2016)
This article is a reflection on violent conflicts in Colombia, taking into account both the position of the actors, and the structural elements conditioning them. The author understands conflict not as a pathology but as a normal space expressing social cleavages. Prom this starting point, the article analyzes the relationship between politics and violence in Colombia, considers its internal and external influences, places emphasis on Colombian political and social exclusion, and describes the possible scenarios in which these conflicts could be resolved.